Konsep Wahyu; Suatu Analis Pemikiran Filosofis - J Juwaini (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Revelation is the most important basis in a religion. The Belief in the revelation is essential for its believers, because God's revelation is a notification received his messengers about religion through a direct or indirect communication. Revelation is also a hidden conversation that can be captured quickly and not composed of letters that require sound waves. The Collection of revelation is a science devoted to the prophet without requiring a learning process. The Knowledge is not gained by a deep thought and  ijtihad but trough the process of a soft feeling which emerges automatically. in the tradition of Islamic philosophy, revelation is considered as a source of knowledge. The knowledge gainedthrough the revelation has a specific status, as the knowledge is receive by the people who has a religious authority, called the Prophet. While the ordinary only people accept the existence of revelation as the pillars of their faith that must be taken for granted.